PENGARUH SISTEM AKUNTANSI PEMERINTAH DAERAH, KOMPETENSI SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN PEGUNUNGAN BINTANG - Tangko, Irmawati; Falah, Syaikhul; Pangayow, Bill J. C. (Fakultas Ekonomi, Universitas Cenderawasih, 2019)
The objectives to be achieved by the authors of this study are: 1) To examine the effect of thelocal government accounting system on the quality of financial reports of Pegunungan BintangDistrict government, 2) To examine the effect of human resource competencies on the quality of theGunung Bintang regency financial statements, 3 ) To examine the effect of technology utilization onthe quality of financial statements of the Pegunungan Bintang District government, and 4) Toexamine the effect of government accounting systems, human resources and the use of informationtechnology on the financial reporting quality of the Pegunungan Bintang District government.This study uses data collection techniques with questionnaires distributed to respondents. Thethe data analysis method used in this study used multiple linear regression analyses.The results showed that the t-test statistics on the government accounting system (SAP) were2,776 with a significance level of 0,007. The statistical value of the tcount test is smaller than t table(2.776> 1.667) with a significantly smaller than Î± = 0.05. Human resources (HR) obtained t teststatistics of 2.662 with a significance level of 0.010. The statistical value of the tcount test is greaterthan t table (2.662> 1.667) and also significantly smaller than Î± = 0.05. The utilization ofinformation technology (PTI) obtained t test statistics of 2.754 with a significance level of 0.008.The statistic value of the tcount test is greater than t table (2.754> 1.667) and also significantlysmaller than Î± = 0.05. The F value of the table at the significance level of 5% (a = 0.05), numerator3 and denominator 66 is equal to 4.896. The calculated F value based on the results of computercalculations is 37,176. When comparing the F count and F table values, it is known that thecalculated F value is greater than the F table value (37,176> 4,896), so that it can be said that thegovernment accounting system, human resources and the use of information technologysimultaneously have a significant effect on report quality regional finance.